Development and Feasibility Study of a Mixed-Mode Solar Dryer for Bankariya, Hetauda, Province-3, Nepal - Basnet, Aakash; Khadka, Nishan; Dhungana, Gaurab; Pradhanang, Aashraf (Kathmandu University Journal of Science, Engineering and Technology, 2020)
Solar Drying is one of the practical and efficient ways to preserve vegetables, fruits, and other crops from spoilage and periodic degradation. Bankariya VDC Hetauda, Province-3, Nepal, where the study was conducted, has been facing the problem of spoilage mainly due to lack of transportation and prevalent effective drying practices. To address the existing situation, basing upon the geographic and economic factors, a mixed-mode solar dryer was fabricated for the locality and the performance of the solar dryer against 2.5 mm slice of fresh ginger was evaluated. The mixed-mode solar dryer showed good results with a percentage time saved of 77.77% and with the cumulative drying rate of 0.0368 kg/h for 1 kg sample and 0.085 kg/h for 2 kg sample, respectively. The mixed-mode solar dried showed promising results for varying sample sizes and could be further upscaled for larger quantities of varying crops.